2015
DOI: 10.1037/a0038907
|View full text |Cite
|
Sign up to set email alerts
|

Only time will tell: The changing relationships between LMX, job performance, and justice.

Abstract: Although it has been argued that leader-member exchange (LMX) is a phenomenon that develops over time, the existing LMX literature is largely cross-sectional in nature. Yet, there is a great need for unraveling how LMX develops over time. To address this issue in the LMX literature, we examine the relationships of LMX with 2 variables known for changing over time: job performance and justice perceptions. On the basis of current empirical findings, a simulation deductively shows that LMX develops over time, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 115 publications
(271 reference statements)
5
50
0
Order By: Relevance
“…We have argued that LMX has a positive effect on employee work engagement and that envy mediates this relationship. These findings support the research of Park, Sturman, Vanderpool, and Chan (2015), as well as Saks' (2006), which indicates that when employees feel that their supervisor is concerned about their personal and professional well-being, they are more likely to reciprocate with vigor, dedication, and absorption; notably, these are the three essential features of work engagement identified by Schaufeli et al (2002). However, the positive effect of LMX on work engagement is weakened by the presence of envy, which verifies arguments made by Tse et al (2013) and Cohen-Charash (2009).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have argued that LMX has a positive effect on employee work engagement and that envy mediates this relationship. These findings support the research of Park, Sturman, Vanderpool, and Chan (2015), as well as Saks' (2006), which indicates that when employees feel that their supervisor is concerned about their personal and professional well-being, they are more likely to reciprocate with vigor, dedication, and absorption; notably, these are the three essential features of work engagement identified by Schaufeli et al (2002). However, the positive effect of LMX on work engagement is weakened by the presence of envy, which verifies arguments made by Tse et al (2013) and Cohen-Charash (2009).…”
Section: Discussionsupporting
confidence: 86%
“…First, a richer understanding of employee emotions, envy in particular, is relevant to workplace management. Leaders should recognize their employees' need for high-quality LMX to mitigate envy and negative behavior, particularly because the contribution of employees to their organization is generally affected by how their immediate supervisors treat them (Kim et al, 2009;Park et al, 2015). Liden and Antonakis (2009) argue that leader distance (both physical and social) may shape the processes by which leaders influence individual, group, or organizational outcomes.…”
Section: Theoretical and Management Implicationsmentioning
confidence: 99%
“…Leader conduct has been perceived as a critical asset in the manager-follower relationship (Dienesch and Liden, 1986). LMX theory implies that leaders create excellent and diverse associations with followers via social exchanges (Park et al, 2015). LMX theory additionally has long documented the significance of fairness in the advancement of LMX (e.g., (Bauer and Green, 1996;Dienesch and Liden, 1986;Graen and Scandura, 1987).…”
Section: Hypotheses Development Perceived Supervisor Support (Pss) Anmentioning
confidence: 99%
“…The theory of LMX hypothesised that leaders are willing to build up exchangerelationships after a certain period with their employee (Alneadi et al, 2020;Park et al, 2015). The role and social exchange theories clarify and reveal how exchange relationships grow progressively over time as a leader associates with each employee and organises their work (Alkheyi et al, 2020;Zhang et al, 2012).…”
Section: Lmx and Stmentioning
confidence: 99%
“…In this situation, ‘role taking’, ‘role making’ and ‘role routinisation’ establish a high-quality LMX relationship ( Zhang Y. et al, 2015 ). Prior studies have stated and empirically shown positive relationships between LMX and individual work outcomes, such as job performance and creativity ( Park et al, 2015 ; Aleksić et al, 2017 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%